(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
This paper reports on a study of publishers’ attitudes towards e-books in the context of the global situation of e-book publishing. Comparative data are drawn from a replication of a survey carried out in Sweden, in Lithuania and in Croatia. The great contrast between the rise of the e-book in English speaking countries (and those with significant English speaking readers) is shown and contrasted with that in ‘small language markets’. This three country survey reveals a number of similar responses from publishers on several key issues, i.e., self-publishing, the future role of bookshops, and relationships with public libraries. The results also reveal that publishers have certain ambivalence on these issues. The overall conclusion is that there is a marked difference in the growth of e-book publishing in small language markets compared with the English language market.